Overexpression of SmMYC2 Increases the Production of Phenolic Acids in Salvia miltiorrhiza - Yang, Na; Zhou, Wenping; Su, Jiao; Wang, Xiaofan; Li, Lin; Wang, Liru; Cao, Xiaoyan; Wang, Zhezhi (Frontiers in Plant Science, 2017)
MYC2 is a core transcription factor in the plant response to jasmonates. It also functions in secondary metabolism and various processes for growth and development. However, the knowledge about its role in Salvia miltiorrhiza is still very limited. We determined that the biosynthesis of salvianolic acid B (Sal B) was strongly induced in two-month-old transgenic plants that over-expressed SmMYC2. In the roots of transgenic line 12 that over-expressed SmMYC2 (OEM-12), the Sal B concentration was as high as 5.95±0.07 mg g-1, a level that was 1.88-fold higher than that in control plants that had been transformed with an empty vector. Neither tanshinone IIA nor cryptotanshinone was detected by HPLC (high-performance liquid chromatography) in any of the genotypes. Global transcriptomic analysis using RNA sequencing revealed that most enzyme-encoding genes for the phenylpropanoid biosynthesis pathway were up-regulated in the overexpression lines. Furthermore, both the phenylalanine and tyrosine biosynthesis pathways were activated in those transgenics. Our data demonstrate that overexpression of SmMYC2 promotes the production of phenolic acids by simultaneously activating both primary and secondary pathways for metabolism in S. miltiorrhiza.